CONCEPTUAL-GNOSEOLOGICAL ASPECTS OF INFORMATION SAFETY (SECURITY) FROM THE POSITION OF SOCIAL ENGINEER-ING - Tarasenko, Y.; Soliannikov, V.; Kalyuzhnyy, A. (Systems and Technologies, 2021)
A possible increase in the reliability of information security in a specific area of human activity is considered from the standpoint of the mandatory performance of regular routine maintenance with strict control of compliance with the code of business conduct in conjunction with the implementation and implementation of systems to ensure the anonymity of the personnel involved, for example, employees of critical facilities or key information infrastructure systems. Analysis of publications on conceptual, organizational, legal, engineering, software and mathematical and their complex aspects of information security of key information infrastructure systems shows that there is still a weak point - the so-called "human factor". This determines the urgency of the problem of generali-zation of the basic principles of information security by implementing an additional system of information security (security) from the standpoint of the use of social engineering. The very concept of "social engineering", symbolically formed in the form of a generalized form of implementation of the engineering approach in the social sphere, should correspond to the specifics of engineering. Therefore, in scientific publications, directly, social engineering, as a special kind of activity, is focused on purposeful change and regulation of various organizational structures (social insti-tutions, formal organizations, etc.). This determines the urgency of the problem of generalization of the basic principles of information security, clarification of the possibility of implementing a system of anonymity of personnel in protection against cyber-attacks through social engineering and, from the standpoint of modern cyber safety, development of rec-ommendations for improving the reliability of information protection. Discerned and revealed in reality the advancement of the hopes of information abduction in a specific hallucination of human activity.